Accelerating tuberculosis vaccine trials with diagnostic and prognostic biomarkers. (3rd August 2017) - Kaufmann, Stefan H.E.; Weiner, January; Maertzdorf, Jeroen
ABSTRACT: Introduction : The most recent estimates on tuberculosis (TB) morbidity and mortality reveal that the global disease burden is even higher than previously assumed. Better drugs, diagnostics and vaccines are major requirements to control the ongoing TB pandemic. The high complexity of the infectious process and the underlying pathology, however, challenge elucidation of protective immune mechanisms at the various stages towards active TB disease, which need to be understood for rational design of novel intervention measures. Areas covered : Next to the more classical approaches, host biomarkers increasingly receive attention as promising tools on our way to control the disease. In the area of diagnosis, host biomarkers are recognized as promising new means because the identification of small biosignatures with high discriminatory and even prognostic potential has stimulated the hope that rapid and easy-to-perform diagnosis and prognosis will become possible in the near future. For rational design of new vaccine candidates, correlates of protection are highly desirable. High-throughput systems-vaccinology will boost the identification of such biomarker profiles. Expert commentary : Considering their potential to accelerate development of better diagnostics and vaccines, host biomarkers should be firmly integrated into future TB research.